2020
DOI: 10.17576/jkmjc-2020-3604-21
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Disaster Communication Management

Abstract: Indonesia is a country that is prone to disasters. To this relation, the government has created the National Disaster Management Agency (BNPB) and the Regional Disaster Management Agency (BPBD) in almost all provinces. However, the magnitude of the potential for disaster causes the government to feel the need for community support in disaster mitigation efforts. Community participation is absolutely necessary. It is in this context that the emergence of the community, in this case, the Garda Caah, is important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In this case, society has an important role in controlling environmental damage according to its wishes. Therefore, community participation is absolutely necessary in disaster mitigation [32]. However, these communities must be equipped with more knowledge and skills through training and mentoring so that they can manage the environment and develop tourism in a sustainable manner.…”
Section: Public/touristmentioning
confidence: 99%
“…In this case, society has an important role in controlling environmental damage according to its wishes. Therefore, community participation is absolutely necessary in disaster mitigation [32]. However, these communities must be equipped with more knowledge and skills through training and mentoring so that they can manage the environment and develop tourism in a sustainable manner.…”
Section: Public/touristmentioning
confidence: 99%
“…In Indonesia, several disaster studies also reveal the involvement of local communities in reducing disaster risk. A study by Rochim et al [34] showed the work of the Garda Caah community volunteer communication network in Bandung, West Java, in improving community-based early warning of the danger of flooding in the city. Likewise, in the case of COVID-19, Prayitno's [35] investigation states the benefits of social capital for community adaptation, primarily through stimulating collective action.…”
Section: Literature Reviewmentioning
confidence: 99%